2020
DOI: 10.1017/s1049096520000840
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Practitioners Want to Connect with Researchers? Evidence from a Field Experiment

Abstract: Researchers often want to increase the broader societal impact of their work. One way to do that is to discuss research findings directly with practitioners. Yet, such interactions are voluntary and do not regularly arise, which raises a key demand question: Under what conditions do practitioners want to connect with researchers? This article shows that relational considerations affect these decisions—that is, what practitioners expect the interaction will be like. I partnered with a US-based civic association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Across all study conditions, the e-mails concluded with an invitation for consultation from the project principal investigator (PI) about evidence-supported policy approaches to addressing ACEs. This invitation was intended to provide relational context, which has been shown experimentally to increase policymaker engagement with research evidence [ 49 , 50 ]. Furthermore, building relationships between researchers and policymakers is frequently identified as one of the most effective ways to facilitate more evidence use by policymakers [ 9 , 44 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all study conditions, the e-mails concluded with an invitation for consultation from the project principal investigator (PI) about evidence-supported policy approaches to addressing ACEs. This invitation was intended to provide relational context, which has been shown experimentally to increase policymaker engagement with research evidence [ 49 , 50 ]. Furthermore, building relationships between researchers and policymakers is frequently identified as one of the most effective ways to facilitate more evidence use by policymakers [ 9 , 44 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The perceived importance of economic evidence and local data is consistent with a larger body of research about attributes of dissemination materials that are important to policymakers [ 7 , 43 – 45 ]. Experiments with state and local legislators in the USA have also tested the effects of manipulating aspects of dissemination materials (e.g., framing of issues in e-mail subject lines [ 46 – 48 ], relational context [ 49 , 50 ], inclusion of maps and narratives [ 51 , 52 ]).…”
Section: Introductionmentioning
confidence: 99%
“…This has often produced a rift between researchers and practitioners with a deficit of mutual trust and understanding. 19,25 The pivot to online learning at the start of the COVID-19 pandemic is a case in point; previous research on pandemics did not encompass the scale or severity of COVID, and research on online learning was similarly oriented to small-scale interventions rather than to moving whole programmes in a matter of days. It might be argued that this was achieved despite the research evidence rather than through meaningful knowledge translation.…”
Section: Are Practitioner Problems Resolvable With Sufficient Evidence?mentioning
confidence: 99%
“…In an ambitious recent effort along these lines, Goerger, Mummolo, and Westwood (2020) sent inquiries to approximately 3,000 local police and sheriff's departments to discuss potential collaborations, following up with all departments that responded affirmatively with offers to develop partnerships at the scholars' expense. Levine (2020b) implemented a similar recruitment model for partnerships with civic organizations. Even with smaller budgets, scholars can be more deliberate in finding jurisdictions dissimilar from those commonly represented in research studies.…”
Section: Recommendations For Using Research Collaborations To Improve...mentioning
confidence: 99%